Thermoplastic resin composition, method for preparing the same, and molded article comprising the same

By developing a thermoplastic resin composition containing specific resins and copolymers, the shortcomings of existing automotive interior materials in terms of heat resistance and chemical resistance are solved, and excellent heat resistance, chemical resistance and mechanical properties are achieved, and suitable for automotive interior materials are achieved.

CN116507676BActive Publication Date: 2025-05-02LG CHEM LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180040344.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-26
Publication Date
2025-05-02
Estimated Expiration
2041-11-26

AI Technical Summary

Technical Problem

Existing automotive interior materials have shortcomings in terms of heat resistance and chemical resistance, especially for commonly used PC/ABS materials, amorphous properties lead to poor chemical resistance and quality problems such as environmental stress cracking (ESC).

Method used

A thermoplastic resin composition is developed, including a polyester resin, a vinyl cyano compound-conjugated diene compound-aromatic vinyl compound graft copolymer, an α-methylstyrene-vinyl cyano compound copolymer, a maleimide polymer and an amide lubricant, and the composition is prepared by melt kneading and extrusion at 200°C to 300°C.

Benefits of technology

The thermoplastic resin composition exhibits excellent heat resistance, chemical resistance, light resistance and noise resistance, while maintaining the same or better mechanical properties as or above conventional heat-resistant ABS resin composition, and has economic advantages and is suitable for automotive interior materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116507676B_ABST
    Figure CN116507676B_ABST
Patent Text Reader

Abstract

The present invention relates to a thermoplastic resin composition, a preparation method thereof and a molded product comprising the thermoplastic resin composition. More particularly, the present invention relates to a thermoplastic resin composition, which comprises a polyester resin (A); a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); an α-methylstyrene-vinyl cyanide compound copolymer (C); a maleimide polymer (D); and an amide lubricant (E), a method for preparing the thermoplastic resin composition, and a molded product comprising the thermoplastic resin composition. The effect of the present invention is to provide a thermoplastic resin composition having excellent heat resistance, chemical resistance, light resistance and noise resistance, while maintaining mechanical properties equal to or better than conventional heat-resistant ABS resin compositions, with huge economic advantages, and therefore, suitable for automotive interior materials due to these favorable features; a method for preparing the thermoplastic resin composition, and a molded product comprising the thermoplastic resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoplastic resin composition, a method for preparing the same, and a molded article comprising the same. More particularly, the present invention relates to a thermoplastic resin composition having excellent heat resistance, chemical resistance, light resistance, and noise resistance while maintaining mechanical properties equal to or better than those of conventional heat-resistant ABS resin compositions, having great economic advantages, and therefore, being suitable for automotive interior materials due to these favorable characteristics; a method for preparing the thermoplastic resin composition; and a molded article comprising the thermoplastic resin composition. Background Art

[0002] ABS resin is an acrylonitrile-butadiene-styrene terpolymer and has excellent impact resistance, rigidity, chemical resistance and processing properties. As a result, ABS resin is used in various fields such as electrical / electronic products, construction and automobiles. However, since ABS resin lacks heat resistance compared to engineering plastics, the use of ABS resin is limited in electrical / electronic product parts and automotive interior materials that require heat resistance.

[0003] Due to its excellent mechanical properties and economy, PC / ABS materials are widely used in various applications such as automobiles and electrical / electronic products. In the case of automobiles, PC / ABS materials are mainly used for automobile interior materials such as center consoles and door interiors. However, since PC / ABS materials have poor chemical resistance due to their amorphous nature, the use of PC / ABS materials is limited. In particular, environmental stress cracking (ESC) of automobile interior materials caused by chemical products is a long-standing and serious quality problem. Therefore, there is an increasing demand for chemical-resistant materials that can prevent cracking caused by chemicals frequently used in automobiles.

[0004] Therefore, there is a need to develop a material that has excellent heat resistance and chemical resistance while maintaining mechanical properties, chemical resistance, light resistance, and noise resistance that are equal to or better than those of existing materials used for automotive interior materials.

[0005] [Related technical literature]

[0006] [Patent Document]

[0007] KR 10-00334710000 B1 Summary of the invention

[0008] Technical issues

[0009] Therefore, the present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a thermoplastic resin composition which has excellent heat resistance, chemical resistance, light resistance and noise resistance while maintaining mechanical properties equal to or better than those of conventional heat-resistant ABS resin compositions, is greatly advantageous in economical aspects, and therefore, is suitable for automotive interior materials due to these favorable characteristics.

[0010] Another object of the present invention is to provide a method for preparing the thermoplastic resin composition.

[0011] Still another object of the present invention is to provide a molded article comprising the thermoplastic resin composition.

[0012] The above and other objects can be achieved by the present invention described below.

[0013] Technical Solution

[0014] According to one aspect of the present invention, a thermoplastic resin composition is provided, which comprises a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D), and an amide lubricant (E).

[0015] According to another aspect of the present invention, a thermoplastic resin composition is provided, which comprises a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D), and an amide lubricant (E), wherein the thermoplastic resin composition comprises 20 wt % to 40 wt % of the polyester resin (A), 15 wt % to 30 wt % of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), 20 wt % to 35 wt % of the α-methylstyrene-vinyl cyanide compound copolymer (C), 10 wt % to 20 wt % of the maleimide polymer (D), or 0.1 wt % to 5 wt % of the amide lubricant (E).

[0016] According to yet another aspect of the present invention, there is provided a thermoplastic resin composition comprising 20 to 40 wt % of a polyester resin (A); 15 to 30 wt % of a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); 20 to 35 wt % of an α-methylstyrene-vinyl cyanide compound copolymer (C); 10 to 20 wt % of a maleimide polymer (D); and 0.1 to 5 wt % of an amide lubricant (E).

[0017] According to another aspect of the present invention, there is provided a thermoplastic resin composition comprising 20 to 40 wt % of a polyester resin (A) having an intrinsic viscosity of 1.1 dl / g or more; 15 to 30 wt % of a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); 20 to 35 wt % of an α-methylstyrene-vinyl cyanide compound copolymer (C); 10 to 20 wt % of a maleimide polymer (D); and 0.1 to 5 wt % of a lubricant (E), wherein the weight of the polyester resin (A) is not less than the weight of the vinyl cyanide compound-conjugated diene compound c aromatic vinyl compound graft copolymer (B).

[0018] According to yet another aspect of the present invention, there is provided a method for preparing a thermoplastic resin composition, the method comprising melt-kneading and extruding a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D), and an amide lubricant (E) at 200° C. to 300° C.

[0019] According to still another aspect of the present invention, there is provided a method for preparing a thermoplastic resin composition, the method comprising melt-kneading and extruding a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D), and an amide lubricant (E) at 200° C. to 300° C., wherein the thermoplastic resin composition comprises 20% to 40% by weight of the polyester resin (A), 15% to 30% by weight of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), 20% to 35% by weight of the α-methylstyrene-vinyl cyanide compound copolymer (C), 10% to 20% by weight of the maleimide polymer (D), or 0.1% to 5% by weight of the amide lubricant (E).

[0020] According to yet another aspect of the present invention, there is provided a method for preparing a thermoplastic resin composition, the method comprising melt-kneading and extruding at 200° C. to 300° C. 20 to 40% by weight of a polyester resin (A); 15 to 30% by weight of a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); 20 to 35% by weight of an α-methylstyrene-vinyl cyanide compound copolymer (C); 10 to 20% by weight of a maleimide polymer (D); and 0.1 to 5% by weight of an amide lubricant (E).

[0021] According to still another aspect of the present invention, provided is a molded article including the thermoplastic resin composition.

[0022] According to another aspect of the present invention, there is provided a method for manufacturing a molded article, the method comprising melt-kneading and extruding at 200°C to 300°C 20 to 40 wt% of a polyester resin (A); 15 to 30 wt% of a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); 20 to 35 wt% of an α-methylstyrene-vinyl cyanide compound copolymer (C); 10 to 20 wt% of a maleimide polymer (D); and 0.1 to 5 wt% of an amide lubricant (E) to prepare pellets, and injecting the prepared pellets using an injection molding machine, wherein, when the injection metering deviation of 30 injections is measured using a 600MT injection molding machine at an injection temperature of 230°C and a mold temperature of 50°C, the molded article has a standard deviation of the injection metering deviation of less than 2.4, or an average value of the injection metering deviation of less than 18.3.

[0023] Beneficial Effects

[0024] The present invention has the effects of providing a thermoplastic resin composition which has excellent heat resistance, chemical resistance, light resistance and noise resistance while maintaining mechanical properties equal to or better than those of conventional heat-resistant ABS resin compositions, is economically advantageous, and is therefore suitable for automotive interior materials due to these favorable features; a method for preparing the thermoplastic resin composition; and a molded article comprising the thermoplastic resin composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A method of measuring environmental stress cracking (ESC) as an indicator of chemical resistance is schematically shown.

[0026] Figure 2 A method of measuring friction noise properties as an index of noise resistance is schematically shown. DETAILED DESCRIPTION

[0027] Hereinafter, a thermoplastic resin composition according to the present invention, a method for preparing the same, and a molded article including the same will be described in detail.

[0028] The present inventors have confirmed that when a polyester resin, a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer, an α-methylstyrene-vinyl cyanide compound copolymer, a maleimide polymer and an amide lubricant are contained in a predetermined composition ratio and the content of the polyester resin is the largest among them, the economic efficiency is excellent compared with the conventional heat-resistant ABS resin composition, the mechanical properties are maintained at a certain level or higher, and the heat resistance, chemical resistance, light resistance and noise resistance required for automobile interior materials are improved. Based on these results, the present inventors have conducted further studies to complete the present invention.

[0029] The thermoplastic resin composition according to the present invention is described in detail as follows.

[0030] The thermoplastic resin composition of the present invention comprises a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D), and an amide lubricant (E). In this case, the thermoplastic resin composition can have excellent heat resistance, chemical resistance, light resistance and noise resistance while maintaining mechanical properties at a certain level or higher, can have excellent economy due to cost reduction, and can therefore be suitable for automotive interior materials.

[0031] In addition, the thermoplastic resin composition of the present invention preferably comprises a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D), and an amide lubricant (E), wherein the thermoplastic resin composition comprises 20 to 40% by weight of the polyester resin (A), 15 to 30% by weight of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), 20 to 35% by weight of the α-methylstyrene-vinyl cyanide compound copolymer (C), 10 to 20% by weight of the maleimide polymer (D), or 0.1 to 5% by weight of the amide lubricant (E). In this case, the thermoplastic resin composition can have excellent heat resistance, chemical resistance, light resistance, and noise resistance while maintaining mechanical properties at a certain level or higher, can have excellent economy due to cost reduction, and can therefore be suitable for automotive interior materials.

[0032] The thermoplastic resin composition of the present invention preferably comprises 20 to 40% by weight of a polyester resin (A); 15 to 30% by weight of a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); 20 to 35% by weight of an α-methylstyrene-vinyl cyanide compound copolymer (C); 10 to 20% by weight of a maleimide polymer (D); and 0.1 to 5% by weight of an amide lubricant (E). In this case, the thermoplastic resin composition can have excellent heat resistance, chemical resistance, light resistance, and noise resistance while maintaining mechanical properties at a certain level or higher, can have excellent economy due to cost reduction, and can therefore be suitable for automotive interior materials.

[0033] Hereinafter, each component of the thermoplastic resin composition of the present invention will be described in detail.

[0034] (A) Polyester resin

[0035] For example, the polyester resin (A) may be included in an amount of 20 to 40 wt%, preferably 25 to 40 wt%, more preferably 25 to 35 wt%, and still more preferably 28 to 31 wt%, based on the total weight of the thermoplastic resin composition. Within this range, chemical resistance, light resistance, and noise resistance may be improved while maintaining mechanical properties and heat resistance equal to or better than conventional heat-resistant ABS resin compositions.

[0036] The polyester resin (A) preferably has an intrinsic viscosity of 1.1 dl / g or more, more preferably 1.1 dl / g to 1.3 dl / g, still more preferably 1.2 dl / g to 1.3 dl / g. Within this range, mechanical properties, processability, impact resistance and noise resistance may be excellent.

[0037] In this specification, when measuring the intrinsic viscosity, unless otherwise specified, the sample to be tested is completely dissolved in dichloromethane, followed by filtration using a filter to obtain a filtrate. Then, using the obtained filtrate, the intrinsic viscosity is measured at 20°C using an Ubbelohde viscometer.

[0038] For example, the polyester resin (A) may include one or more selected from polyethylene adipate (PEA), polybutylene succinate (PBS), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT) and polyethylene naphthalate (PEN), preferably polybutylene terephthalate. In this case, the overall mechanical properties of the composition can be good, the physical property balance can be excellent, and it can be easily molded.

[0039] As the polybutylene terephthalate resin, a general polybutylene terephthalate resin may be used without particular limitation. For example, the polybutylene terephthalate resin may be a polymer obtained by polycondensation of 1,4-butanediol and dimethyl terephthalate.

[0040] As a method for preparing the polyester resin, a preparation method commonly used in the field to which the present invention belongs may be adopted without particular limitation.

[0041] (B) Vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer

[0042] For example, the graft copolymer (B) may be included in an amount of 15 to 30 wt %, preferably 20 to 30 wt %, more preferably 25 to 30 wt %, still more preferably 26 to 29 wt %, most preferably 26 to 27 wt %, based on the total weight of the thermoplastic resin composition. Within this range, mechanical properties and thermal stability may be maintained at a certain level, and chemical resistance, light resistance, and noise resistance may be excellent.

[0043] For example, the graft copolymer (B) may be a graft copolymer obtained by graft-polymerizing 10 to 40% by weight of an aromatic vinyl compound and 1 to 20% by weight of a vinyl cyanide compound onto 40 to 80% by weight of a conjugated diene rubber, preferably a graft copolymer obtained by graft-polymerizing 20 to 35% by weight of an aromatic vinyl compound and 1 to 15% by weight of a vinyl cyanide compound onto 50 to 70% by weight of a conjugated diene rubber, and more preferably a graft copolymer obtained by graft-polymerizing 25 to 35% by weight of an aromatic vinyl compound and 5 to 15% by weight of a vinyl cyanide compound onto 55 to 65% by weight of a conjugated diene rubber. Within this range, mechanical properties and processability may be excellent.

[0044] For example, the graft copolymer (B) may have a grafting degree of 30 to 50%, preferably 35 to 45%. Within this range, mechanical properties and processability may be excellent.

[0045] In this specification, in order to measure the grafting degree, the grafted polymer latex was coagulated, washed and dried to obtain a powdered latex, and then 2 g of the obtained powder was added to 300 ml of acetone, followed by stirring for 24 hours. Then, an ultracentrifuge was used to separate the stirred solution, and methanol was added dropwise to the separated acetone solution to obtain an ungrafted portion, followed by drying at 60° C. to 120° C. Thereafter, the weight of the dried ungrafted portion was measured, and the grafting degree was calculated by substituting the measured weight value into the following equation 1.

[0046] [Equation 1]

[0047] Grafting degree (%) = (weight of monomer grafted onto rubber polymer / total weight of copolymer) × 100

[0048] For example, the conjugated diene rubber may have to Best to More preferred to Within this range, mechanical properties and processing properties can be improved.

[0049] In this specification, unless otherwise specified, the average particle size can be measured by dynamic light scattering, specifically, it can be measured as an intensity value using a Nicomp 380 particle size analyzer (manufacturer: PSS) in Gaussian mode. As a specific measurement example, a sample can be prepared by diluting 0.1 g of latex (TSC: 35 wt% to 50 wt%) with distilled water by 1,000 to 5,000 times, that is, the sample is appropriately diluted so that it does not significantly deviate from the intensity setpoint of 300 kHz, and placed in a glass tube. Then, the average particle size of the sample is measured using a flow cell in auto-dilution in the measurement mode of dynamic light scattering / intensity 300 kHz / intensity-weight Gaussian analysis. At this time, the setting values ​​are as follows: temperature: 23°C; measurement wavelength: 632.8 nm.

[0050] For example, the graft copolymer (B) may have a weight average molecular weight of about 70,000 to about 100,000 g / mol, preferably about 75,000 to about 85,000 g / mol. Within this range, processability and impact resistance may be excellent due to appropriate fluidity.

[0051] In this specification, tetrahydrofuran (THF) is used as an eluent and a gel permeation chromatograph (GPC) filled with porous silica as a column filling material is used to measure the weight average molecular weight at 40° C. In this case, the weight average molecular weight is obtained as a relative value to a polystyrene (PS) standard sample.

[0052] The weight of the polyester resin (A) is preferably not less than the weight of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B). More preferably, the weight of the polyester resin (A) is greater than the weight of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B). In this case, the mechanical properties can be maintained at a certain level or higher, and the heat resistance, chemical resistance, light resistance and noise resistance can be excellent. In addition, according to the cost reduction, the economy can be excellent. Therefore, the composition of the present invention can be suitable as an automotive interior material.

[0053] In the present specification, for example, the conjugated diene compound may include one or more selected from the group consisting of 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, and isoprene.

[0054] In the present specification, for example, the vinyl cyanide compound may be acrylonitrile, methacrylonitrile or a mixture thereof.

[0055] In the present specification, the aromatic vinyl compound may include one or more selected from styrene, alpha (α) -methylstyrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, ethylstyrene, isobutylstyrene, tert-butylstyrene, o-bromostyrene, p-bromostyrene, m-bromostyrene, o-chlorostyrene, p-chlorostyrene, m-chlorostyrene, vinyltoluene, vinylxylene, fluorostyrene and vinylnaphthalene.

[0056] As a method for preparing the graft copolymer (B), the preparation method commonly used in the field to which the present invention belongs can be adopted without particular limitation. For example, the graft copolymer (B) can be prepared by suspension polymerization, emulsion polymerization, solution polymerization or bulk polymerization, preferably emulsion polymerization.

[0057] (C) α-Methylstyrene-vinyl cyanide copolymer

[0058] The α-methylstyrene-vinyl cyanide compound copolymer (C) is preferably included in an amount of 20 to 35 wt %, more preferably 20 to 30 wt %, still more preferably 25 to 30 wt %, still more preferably 26 to 29 wt %, most preferably 26 to 27 wt %, based on the total weight of the thermoplastic resin composition. Within this range, mechanical properties and friction resistance can be maintained at a certain level or higher, and heat resistance can be excellent.

[0059] The α-methylstyrene-vinyl cyanide compound copolymer (C) preferably contains 65 to 85% by weight of α-methylstyrene and 15 to 35% by weight of the vinyl cyanide compound, more preferably 65 to 80% by weight of α-methylstyrene and 20 to 35% by weight of the vinyl cyanide compound, still more preferably 70 to 80% by weight of α-methylstyrene and 20 to 30% by weight of the vinyl cyanide compound, still more preferably 65 to 85% by weight of α-methylstyrene and 25 to 30% by weight of the vinyl cyanide compound. Within this range, mechanical properties and friction resistance can be maintained at a certain level or more, and heat resistance can be excellent.

[0060] As another preferred example, the α-methylstyrene-vinyl cyanide compound copolymer (C) may contain 65 wt % to 85 wt % of α-methylstyrene, 15 wt % to 35 wt % of a vinyl cyanide compound, and 0 wt % to 10 wt % of an aromatic vinyl compound (however, excluding α-methylstyrene). Within this range, mechanical properties and friction resistance may be maintained at a certain level or higher, and heat resistance may be excellent.

[0061] The α-methylstyrene-vinyl cyanide compound copolymer (C) preferably has a branching degree of 0.40 to 0.60. Within this range, mechanical properties and friction resistance can be maintained at a certain level or higher, and heat resistance can be excellent.

[0062] In this specification, the degree of branching can be obtained by measuring the molecular weight and the radius of gyration (RG) using multi-angle laser light scattering (MALLS), plotting Log RG against Log Mw and calculating the slope. Here, when the degree of branching is 1, branching does not occur (linear). When the degree of branching is 0.3, a large amount of branching occurs and cross-linking occurs (spherical). As the degree of branching approaches 0.3, the number of branches in the polymer increases.

[0063] For example, the α-methylstyrene-vinyl cyanide compound copolymer (C) may have a weight average molecular weight of 80,000 to 200,000 g / mol, preferably 90,000 to 150,000 g / mol. Within this range, mechanical properties and friction resistance may be maintained at a certain level or higher, and heat resistance may be excellent.

[0064] In this specification, the weight average molecular weight (Mw) can be obtained as a relative value of a polystyrene (PS) standard sample using a gel permeation chromatograph (GPC, Waters Breeze).

[0065] The α-methylstyrene-vinyl cyanide compound copolymer (C) preferably has a glass transition temperature (Tg) of 124° C. to 140° C. Within this range, mechanical properties and friction resistance may be maintained at a certain level or higher, and heat resistance may be excellent.

[0066] In the present specification, the glass transition temperature (Tg) can be measured using Pyris 6DSC (Perkin Elmer Co.).

[0067] The α-methylstyrene-vinyl cyanide compound copolymer (C) preferably has a residual monomer content measured by gas chromatography (GC) of 500 ppm or less, more preferably 450 ppm or less, still more preferably 350 ppm to 450 ppm. Within this range, flexural strength, flexural modulus, heat resistance and light resistance may be excellent.

[0068] In this specification, when measuring the residual monomer content, 2g of copolymer was dissolved in 10mL of chloroform and precipitated with 30ml of methanol to obtain the supernatant of the copolymer. The supernatant was filtered with a 0.2μm disc syringe filter. Then, the residual oligomer content was measured using gas chromatography (GC), and the results were analyzed using an automatic liquid sampler-gas chromatography / flame ionization detector (ALS-GC / FID).

[0069] For example, the α-methylstyrene-vinyl cyanide compound copolymer (C) may have a bulk density of 0.20 to 0.35 g / cc, preferably 0.22 to 0.33 g / cc. Within this range, there are advantages in storage and transportation.

[0070] In this specification, bulk density (g / cc) may be calculated by dividing the weight of powder in a 100 cc cup in grams (g) by 100, and may be expressed in units of g / cc.

[0071] As a method for preparing the α-methylstyrene-vinyl cyanide compound copolymer (C), the preparation method commonly used in the field to which the present invention belongs can be adopted without particular limitation. As a specific example, it can include adding 0.05 to 0.5 parts by weight of a multifunctional initiator to 100 parts by weight of a monomer mixture containing 65 to 85% by weight of α-methylstyrene and 15 to 35% by weight of a vinyl cyanide compound, and performing a polymerization step. In this case, the polymerization can be suspension polymerization, emulsion polymerization, solution polymerization or bulk polymerization, preferably bulk polymerization. In this case, heat resistance and fluidity can be excellent.

[0072] (D) Maleimide polymers

[0073] The maleimide polymer (D) is a polymer containing a repeating unit derived from a maleimide compound. In this case, mechanical properties and heat resistance can be improved.

[0074] The maleimide-based polymer (D) is preferably included in an amount of 10 to 20 wt %, more preferably 15 to 20 wt %, still more preferably 15 to 19 wt %, still more preferably 16 to 19 wt %, based on the total weight of the thermoplastic resin composition. Within this range, mechanical properties, thermal stability and friction resistance can be maintained at a certain level, environmental stress cracking (ESC) can be prevented, and injection moldability can be excellent.

[0075] For example, the maleimide polymer (D) may contain 20 wt % or more, preferably 20 wt % to 60 wt %, more preferably 30 wt % to 60 wt %, still more preferably 40 wt % to 60 wt %, still more preferably 45 wt % to 55 wt % of a maleimide monomer. Within this range, mechanical properties and heat resistance may be excellent.

[0076] The maleimide polymer (D) is preferably a copolymer comprising N-(substituted) maleimide and an aromatic vinyl compound, and more preferably a copolymer comprising N-(substituted) maleimide; an unsaturated dicarboxylic acid or anhydride thereof; and an aromatic vinyl compound. Within this range, mechanical properties and heat resistance can be excellent.

[0077] As a preferred example, the maleimide polymer (D) may include 45 wt % to 55 wt % of a maleimide compound; 40 wt % to 50 wt % of an aromatic vinyl compound; and 1 wt % to 10 wt % of maleic acid or its anhydride. Within this range, mechanical properties and heat resistance may be excellent.

[0078] The maleimide compound is preferably maleimide or N-(substituted)maleimide, more preferably N-(substituted)maleimide, and as a specific example, may include one or more selected from N-methylmaleimide, N-ethylmaleimide, N-cyclohexylmaleimide and N-phenylmaleimide, within this range, the mechanical properties and heat resistance may be excellent.

[0079] The maleimide-based polymer (D) preferably has a weight average molecular weight of about 80,000 g / mol to about 200,000 g / mol. Within this range, mechanical properties and heat resistance may be excellent.

[0080] The maleimide-based polymer (D) preferably has a glass transition temperature of 140 to 210° C., more preferably 180 to 210° C., still more preferably 190 to 205° C. Within this range, mechanical properties and heat resistance may be excellent.

[0081] As a method for preparing the maleimide polymer (D), the preparation method commonly used in the field to which the present invention belongs can be adopted without particular limitation. For example, the maleimide polymer (D) can be prepared by suspension polymerization, emulsion polymerization, solution polymerization or bulk polymerization, preferably bulk polymerization.

[0082] (E) Amide lubricants

[0083] The amide lubricant (E) is preferably contained in an amount of 0.1 to 5 wt %, more preferably 0.1 to 3 wt %, still more preferably 0.1 to 2.5 wt %, still more preferably 0.1 to 2.0 wt %, still more preferably 0.3 to 2.0 wt %, most preferably 0.5 to 2.0 wt %, based on the total weight of the thermoplastic resin composition. Within this range, injection moldability can be excellent without causing deterioration of mechanical properties. In particular, in injection metering, metering time (seconds) and deviation per injection can be reduced.

[0084] The amide-based lubricant (E) is preferably a fatty acid amide-based lubricant. In this case, injection moldability can be excellent.

[0085] The fatty acid amide lubricant preferably includes one or more selected from stearamide, behenic acid amide, ethylenebis(stearamide), N,N'-ethylenebis(12-hydroxystearamide), erucic acid amide, oleamide and ethylenebisoleamide, more preferably ethylenebis(stearamide). Within this range, injection moldability can be excellent without causing deterioration of mechanical properties.

[0086] Thermoplastic resin composition

[0087] The thermoplastic resin composition preferably has a standard deviation of injection metering deviation of 2.4 or less, more preferably 2.0 or less, still more preferably 1.2 or less, still more preferably less than 1.0, when injection metering deviation of 30 shots is measured using a 600MT injection molding machine at an injection temperature of 230°C and a mold temperature of 50°C. Within this range, physical properties are balanced and injection molding processability can be excellent.

[0088] The thermoplastic resin composition preferably has a fluidity (melt flow rate) of 10 to 25 g / 10 min, more preferably 10 to 20 g / 10 min, still more preferably 11 to 16 g / 10 min, still more preferably 12 to 14 g / 10 min, as measured under conditions of 260° C. and 5 kg according to ISO 1133. Within this range, physical property balance, processability and injection moldability may be excellent.

[0089] The thermoplastic resin composition preferably has an average value of injection metering deviation of 18.3 or less, more preferably 18.1 or less, still more preferably 16 or less, still more preferably 14 or less, and most preferably less than 13.5, when injection metering deviation of 30 shots is measured using a 600 MT injection molding machine at an injection temperature of 230° C. and a mold temperature of 50° C. Within this range, physical properties are balanced and injection moldability can be excellent.

[0090] The thermoplastic resin composition preferably has a heat distortion temperature of 108° C. or higher, as a specific example, 108° C. to 110° C., measured at 0.45 MPa according to ISO 75. Within this range, physical properties are balanced and heat resistance may be excellent.

[0091] The thermoplastic resin composition preferably has a heat distortion temperature of 88° C. or higher, as a specific example, 88° C. to 100° C., preferably 88° C. to 95° C., measured at 1.82 MPa according to ISO 75. Within this range, physical properties are balanced and heat resistance may be excellent.

[0092] The thermoplastic resin composition preferably has a flexural strength of 66 MPa or more and a flexural modulus of 1,950 MPa or more, and as a specific example, a flexural strength of 66 MPa to 70 MPa and a flexural modulus of 1,950 MPa to 2,020 MPa, when the flexural strength and the flexural modulus are measured using a 1 / 8″ thick test specimen under the conditions of a span of 64 mm and a test speed of 2 mm / min according to ISO 178. Within this range, physical properties are balanced and mechanical strength may be excellent.

[0093] For example, in the case of a thermoplastic resin composition, when the temperature is 89±3°C, the relative humidity is 50±5%, and the concentration is 84 MJ / m 2 The radiation dose and 0.55±0.02W / m 2When irradiated under the conditions of an irradiance of 1.000 nm (wavelength range: 300 nm to 400 nm), the glossy specimen may have a color difference change (ΔE) of 1.2 or less, preferably 1.1 or less, more preferably 0.5 to 1.1. Within this range, the balance of all physical properties may be excellent.

[0094] In this specification, when the color difference (ΔE) is measured, the color of the sample is determined using a Hunter Lab colorimeter, and ΔE is calculated by the following Equation 3.

[0095] [Equation 3]

[0096]

[0097] In addition, in the case of a thermoplastic resin composition, when subjected to a temperature of 89±3°C, a relative humidity of 50±5%, and a relative humidity of 84 MJ / m 2 The radiation dose and 0.55±0.02W / m 2 When irradiated under the conditions of an irradiance of 100 nm to 400 nm (wavelength range: 300 nm to 400 nm), the embossed sample may have a color difference (ΔE) of 0.9 or less, preferably 0.5 to 0.9. Within this range, the balance of all physical properties may be excellent.

[0098] In this specification, a sample for measuring light resistance is prepared using a mold mirror-processed with 2,000 to 40,000 grit at an injection temperature of 230 to 250° C. and a mold temperature of 50° C. The embossed sample is prepared in the same manner as the above sample except that a mold having an embossed pattern having a size of 15 μm to 21 μm formed on its surface is used.

[0099] Generally, in the case of conventional thermoplastic resin compositions used as automotive interior materials, the glossy specimen and the embossed specimen have a color difference (ΔE) of 2 or less as measured according to MS210-05 or ISO 105. In the case of the thermoplastic resin composition according to the present invention, the glossy specimen and the embossed specimen have a color difference (ΔE) of 1.2 or less and a color difference (ΔE) of 1.0 or less, respectively. That is, the color difference of the thermoplastic resin composition of the present invention is significantly lower than that of the conventional thermoplastic resin composition, indicating that the thermoplastic resin composition of the present invention has excellent light resistance compared to the conventional thermoplastic resin composition.

[0100] For example, when a specimen having a size (length: 165 mm, width: 19 mm, thickness: 3.2 mm) equal to that of a tensile strength test specimen according to ASTM D638 is fixed to a fixture having a stress of 2.0% according to an environmental stress cracking (ESC) experiment, 25 μl of an air freshener (containing a mixed solution of isoamyl acetate, limonene and linalool at a volume ratio of 4:1:1) is applied to the specimen using a micropipette, and then, after 2 hours, the occurrence of cracks or cracks is observed, and the thermoplastic resin composition may have no cracks or cracks. Within this range, the balance of all physical properties may be excellent.

[0101] In this specification, environmental stress cracking is related to chemical resistance and refers to a phenomenon in which cracks and breaks occur on the surface of plastic when the plastic comes into contact with chemicals in the presence of continuous internal and external stresses.

[0102] Down Figure 1 A method for measuring environmental stress cracking is schematically shown, and a series of steps are shown, in which an air freshener is applied to a specimen having a size equal to that of a tensile strength test specimen according to ASTM D638, the specimen is fixed to a fixture with a stress of 2.0%, and then, the surface of the specimen is observed after 2 hours. The surface of the specimen without cracks or cracks is marked as "normal". The surface of the specimen with cracks or cracks is marked as "cracks & cracks". The specimen that was broken due to cracks is marked as "cracks & broken". In addition, Figure 1 The right figure schematically shows the process of generating cracks or fissures on the surface of the sample and causing the sample to break.

[0103] For example, the thermoplastic resin composition has a thermal conductivity of 15 kJ / m 2 Above, preferably 20 kJ / m 2 The above Izod impact strength is, as a specific example, 15 kJ / m 2 Up to 25kJ / m 2 , preferably 20kJ / m 2 Up to 25kJ / m 2 Within this range, the balance of all physical properties can be excellent.

[0104] For example, the thermoplastic resin composition may have a tensile strength of 37 MPa or more, preferably 37 MPa to 45 MPa, more preferably 40 MPa to 43 MPa, measured at 50 mm / min according to ISO 527. Within this range, the balance of all physical properties may be excellent.

[0105] For example, the thermoplastic resin composition may have an elongation of 37% or more, preferably 40% or more, and as a specific example, 37% to 45% measured at 50 mm / min according to ISO 527. Within this range, the balance of all physical properties may be excellent.

[0106] For example, the thermoplastic resin composition may have a hardness of 1.11 g / cm 3 Below, preferably 1.00g / cm 3 Up to 1.11g / cm 3 Within this range, the weight can be reduced and the balance of all physical properties can be excellent.

[0107] For example, when acceleration, pulse, frequency, friction, and fluctuation are measured using a Ziegler SSP-04 under the conditions of a specimen load of 10 N and a motion condition of 1 mm / s using a flat specimen having a size of 70 mm×60 mm and a flat specimen having a size of 25 mm×50 mm, and a risk factor (RPN) value (which represents friction noise performance) is calculated by the following equation 2, the thermoplastic resin composition may have a risk factor (RPN) value of 3 or less, preferably 1 to 3. Within this range, the balance of all physical properties and noise resistance may be excellent.

[0108] For example, when acceleration, pulse, frequency, friction, and fluctuation are measured using a Ziegler SSP-04 under the conditions of a specimen load of 10 N and a motion condition of 4 mm / s using a flat specimen having a size of 70 mm×60 mm and a flat specimen having a size of 25 mm×50 mm, and a risk factor (RPN) value (which represents friction noise performance) is calculated by the following equation 2, the thermoplastic resin composition may have a risk factor (RPN) value of 2 or less, preferably 1 to 2. Within this range, the balance of all physical properties and noise resistance may be excellent.

[0109] For example, when acceleration, pulse, frequency, friction, and fluctuation are measured using a Ziegler SSP-04 under the conditions of a specimen load of 40 N and a motion condition of 1 mm / s using a flat specimen having a size of 70 mm×60 mm and a flat specimen having a size of 25 mm×50 mm, and a risk factor (RPN) value representing friction noise performance (stick-slip noise) is calculated by the following equation 2, the thermoplastic resin composition may have a risk factor (RPN) value of 2 or less, preferably 1 to 2. Within this range, the balance of all physical properties and noise resistance may be excellent.

[0110] For example, when acceleration, pulse, frequency, friction, and fluctuation are measured using a Ziegler SSP-04 under the conditions of a specimen load of 40 N and a motion condition of 4 mm / s using a flat specimen having a size of 70 mm×60 mm and a flat specimen having a size of 25 mm×50 mm, and a risk factor (RPN) value representing friction noise performance (stick-slip noise) is calculated by the following equation 2, the thermoplastic resin composition may have a risk factor (RPN) value of 1 or less. Within this range, the balance of all physical properties and noise resistance may be excellent.

[0111] [Equation 2]

[0112]

[0113] <Evaluation of friction noise performance>

[0114] RPN is 1 or more and 3 or less: Good (the probability of friction noise generation is very low)

[0115] RPN is 4 or more and 5 or less: Partially good

[0116] RPN is 6 or more and 10 or less: Not good

[0117] In the present invention, friction noise performance is related to buzz, squeak and rattle (BSR) generated in the vehicle and is a performance associated with aesthetics. Friction noise occurs at the assembly seams, joints or friction areas of the system and is also called noise. Here, buzz is caused by structural vibration and is a drum-like noise generated by the part panel, squeak is noise generated by friction in the shear direction between parts, and rattle is noise generated by vertical collision between parts.

[0118] Down Figure 2 The method of measuring friction noise performance using Ziegler SSP-04 is schematically shown. The friction noise performance is measured under four conditions of (10N, 1mm / s), (10N, 4mm / s), (40N, 1mm / s) and (40N, 4mm / s) using a flat sample with a size of 70mm×60mm and a flat sample with a size of 25mm×50mm.

[0119] The thermoplastic resin composition preferably includes 0.1 wt % to 5 wt % of one or more selected from antioxidants and UV absorbers. Within this range, processability, light resistance, noise resistance, and chemical resistance may be improved.

[0120] For example, the antioxidant may be a phenolic antioxidant, a phosphorus antioxidant or a mixture thereof, preferably a phenolic antioxidant. In this case, oxidation due to heat during extrusion can be prevented, and mechanical properties and heat resistance can be excellent.

[0121] For example, the phenolic antioxidant may include one or more selected from N, N'-hexane-1,6-diyl-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl propionamide)], pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], N, N'-hexamethylene-bis(3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid amide), triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate], 3,5-di-tert-butyl-4-hydroxybenzilphosphonate-diethyl ester, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzil) benzene and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzil) isocyanurate. In this case, heat resistance can be greatly improved while maintaining the balance of physical properties at a high level.

[0122] For example, the phosphorus antioxidant may include a member selected from triphenyl phosphite, tris(nonylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris(2,6-di-tert-butylphenyl) phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, One or more of phenyl ester, monooctyl diphenyl phosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, bis(nonylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butyl-phenyl)pentaerythritol diphosphite, octadecyl pentaerythritol diphosphite, tributyl phosphate, triethyl phosphate and trimethyl phosphate.

[0123] The antioxidant is preferably included in an amount of 0.05 wt % to 1.0 wt %, more preferably 0.1 wt % to 0.7 wt %, and still more preferably 0.1 wt % to 0.5 wt %, based on the total weight of the thermoplastic resin composition. Within this range, the balance of physical properties can be excellent and heat resistance can be improved.

[0124] For example, the UV absorber may include one or more selected from triazine UV absorbers, benzophenone UV absorbers, benzotriazole UV absorbers, quinolinone UV absorbers, benzoate UV absorbers, cyanoacrylate UV absorbers and benzoxazole UV absorbers, preferably benzotriazole UV absorbers. In this case, the physical property balance can be excellent and the light resistance can be further improved.

[0125] For example, the triazine UV absorber may include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,6-diphenyl-4-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine. 5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxyphenyl)-1,3,5-triazine) )-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-oct ...6-Tris(2-hydroxy-3-methyl-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, One or more of 2-(4,6-diphenyl-1,3,5-triazine, 2-(2-ethylhexanoyloxy)ethoxy)phenol, 2-(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropane-2-yloxy)phenyl)-1,3,5-triazine, 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-N-octyloxyphenyl)-1,3,5-triazine and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(2-(2-ethylhexanoyloxy)ethoxy)phenol.

[0126] For example, the benzophenone-based UV absorber may include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfonyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxytrihydratebenzophenone, 2-hydroxy-4-dodecyloxy-benzophenone, 2-hydroxy-4- ... One or more of octaalkoxy-benzophenone, 2,2′-dihydroxy-4-methoxybenzophenone, 2,2′,4,4′-tetrahydroxybenzophenone, 2,2′-dihydroxy-4,4′-dimethoxybenzophenone, 2,2′-dihydroxy-4,4′-dimethoxy-5-sodiumsulfoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-methoxy-2′-carboxybenzophenone and 4,4′-bis(diethylamino)benzophenone.

[0127] For example, the benzotriazole UV absorber may include 2-(2′-hydroxy-5′-methylphenyl)benzotriazole, 2′-hydroxy-3′, 2-(2′-hydroxy-3′-tert-butyl-5′-methylphenyl)benzotriazole, 2-(2′-hydroxy-5′-methylphenyl)benzotriazole, 5′-bis(α,α-dimethylbenzil)phenyl-benzotriazole, 2-(2′-hydroxy-3′,5′-di-tert-butyl-phenyl)-benzotriazole, 2-(2′-hydroxy-3′-tert-butyl-5′-methylphenyl)-5-chlorobenzotriazole, 2-(2′-hydroxy-3′,5′-di-tert-butyl-phenyl)- One or more of 5-chlorobenzotriazole, 2-(2′-hydroxy-3′, 5′-di-tert-pentyl)-benzotriazole, 2-(2′-hydroxy-3′, 5′-di-tert-pentylphenyl)-5-chlorobenzotriazole, 2-(2′-hydroxy-3′-(3″, 4″, 5″, 6″-tetrahydrophthalimidomethyl)-5′-methylphenyl)benzotriazole, 2-(2-hydroxy-3, 5-di-tert-pentylphenyl), 2-(2′-hydroxy-5′-tert-octylphenyl)benzotriazole and 2,2′-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol.

[0128] For example, the indole-based UV absorber may be 2-[(1-methyl-2-phenyl-1H-indol-3-yl)methylene]malononitrile.

[0129] For example, the quinolinone-based UV absorber may be 4-hydroxy-3-[(phenylimino)methyl]-2(1H)-quinolinone.

[0130] For example, the benzoate UV absorber may include one or more selected from 2,4-di-tert-butylphenyl-3′,5′-di-tert-butyl-4′-hydroxybenzoate, 2,6-di-tert-butylphenyl-3′,5′-di-tert-butyl-4′-hydroxybenzoate, n-hexadecyl-3,5-di-tert-butyl-4-hydroxybenzoate and n-octadecyl-3,5-di-tert-butyl-4-hydroxybenzoate.

[0131] For example, the cyanoacrylate-based UV absorber may be 2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, or a mixture thereof.

[0132] The UV absorber is preferably included in an amount of 0.05 wt % to 1.0 wt %, more preferably 0.1 wt % to 0.7 wt %, still more preferably 0.1 wt % to 0.5 wt %, based on the total weight of the thermoplastic resin composition. Within this range, the balance of physical properties can be excellent and light resistance can be further improved.

[0133] Method for preparing thermoplastic resin composition

[0134] The method for preparing the thermoplastic resin composition of the present invention comprises the steps of melt-kneading and extruding a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D) and an amide lubricant (E) at 200° C. to 300° C. In this case, the thermoplastic resin composition can have excellent heat resistance, chemical resistance, light resistance and noise resistance while maintaining mechanical properties at a certain level or higher, can be greatly advantageous in economic terms, and therefore, can be suitable for automotive interior materials due to these favorable characteristics.

[0135] In addition, the method for preparing the thermoplastic resin composition of the present invention preferably includes the steps of melt-kneading and extruding a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D) and an amide lubricant (E) at 200° C. to 300° C., wherein the thermoplastic resin composition contains 20% to 40% by weight of the polyester resin (A); 15% to 30% by weight of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); 20% to 35% by weight of the α-methylstyrene-vinyl cyanide compound copolymer (C); 10% to 20% by weight of the maleimide polymer (D); or 0.1% to 5% by weight of the amide lubricant (E). In this case, the thermoplastic resin composition can have excellent heat resistance, chemical resistance, light resistance, and noise resistance while maintaining mechanical properties at a certain level or higher, can be greatly advantageous in economic terms, and therefore, can be suitable for automotive interior materials due to these favorable features.

[0136] In addition, more preferably, the method for preparing the thermoplastic resin composition of the present invention includes the steps of melt-kneading and extruding 20 wt % to 40 wt % of polyester resin (A); 15 wt % to 30 wt % of vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); 20 wt % to 35 wt % of α-methylstyrene-vinyl cyanide compound copolymer (C); 10 wt % to 20 wt % of maleimide polymer (D); and 0.1 wt % to 5 wt % of amide lubricant (E) at 200° C. to 300° C. In this case, the thermoplastic resin composition can have excellent heat resistance, chemical resistance, light resistance and noise resistance while maintaining mechanical properties at a certain level or higher, can be greatly advantageous in economic terms, and therefore, can be suitable for automotive interior materials due to these favorable characteristics.

[0137] For example, the method of preparing the thermoplastic resin composition may include the step of preparing a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer (B).

[0138] For example, the steps of preparing the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer (B) can be the steps of adding 70 to 200 parts by weight of deionized water, 0.1 to 2 parts by weight of an initiator, 0.1 to 2 parts by weight of an emulsifier and 0.05 to 1.5 parts by weight of a molecular weight regulator to a total of 100 parts by weight of a conjugated diene rubber latex, an aromatic vinyl compound and a vinyl cyanide compound to carry out polymerization; terminating the polymerization at a polymerization conversion rate of 93 to 99% by weight to obtain a graft copolymer latex; and coagulating, dehydrating and drying the graft copolymer latex.

[0139] As a specific example, the step of preparing the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer (B) may be to mix in a separate mixing device 10 to 40 wt % of the aromatic vinyl compound, 1 to 20 wt % of the vinyl cyanide compound, 10 to 50 wt % of deionized water, 0.09 to 1.5 wt % of an initiator, 0.1 to 2 wt % of an emulsifier and 0.5 to 1 wt % of an aqueous solution of 1% to 40 wt % based on 100 wt % of the conjugated diene rubber, the aromatic vinyl compound and the vinyl cyanide compound in total. A mixed solution of 0.05 to 1.5 parts by weight of a molecular weight regulator is added to 40 to 80 weight % (based on solids) of a conjugated diene rubber latex and 60 to 150 parts by weight of deionized water at 65 to 75° C. for 2 to 4 hours; 0.01 to 0.5 parts by weight of an initiator is added thereto; the temperature is raised to 75 to 80° C. for 30 to 90 minutes; the graft polymerization is terminated at a polymerization conversion rate of 93 to 99 weight % to obtain a graft copolymer latex; and the graft copolymer latex is coagulated, dehydrated and dried. In this case, mechanical properties and processing properties can be excellent.

[0140] In the present specification, as a method for measuring the polymerization conversion rate, a measuring method generally used in the field to which the present invention pertains may be employed without particular limitation.

[0141] For example, the conjugated diene rubber latex included in the preparation of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer (B) can be prepared by adding 30 to 100 parts by weight of deionized water, 0.5 to 3 parts by weight of an emulsifier, 0.01 to 0.5 parts by weight of an electrolyte, 0.1 to 0.5 parts by weight of a molecular weight regulator, and 0.1 to 1 parts by weight of an initiator to 100 parts by weight of a conjugated diene compound for polymerization. In this case, the impact resistance can be excellent.

[0142] As another example, the conjugated diene rubber latex can be prepared by adding 40 to 70 parts by weight of deionized water, 1 to 2.5 parts by weight of an emulsifier, 0.05 to 0.3 parts by weight of an electrolyte, 0.2 to 0.4 parts by weight of a molecular weight regulator, and 0.3 to 0.8 parts by weight of an initiator to 100 parts by weight of a conjugated diene compound for polymerization. In this case, impact resistance can be excellent.

[0143] For example, the emulsifier used in preparing the graft copolymer latex and / or the conjugated diene rubber latex may include one or more selected from rosin acid metal salts, alkyl aryl sulfonates, basic methyl alkyl sulfates, sulfonated alkyl esters and metal salts of unsaturated fatty acids.

[0144] For example, the electrolyte used in preparing the graft copolymer latex and / or the conjugated diene rubber latex may include an electrolyte selected from KCl, NaCl, KHCO 3 、NaHCO 3 , K 2 CO 3 、Na 2 CO 3 , KHSO 3 、NaHSO 3 , K 4 P 2 O 7 、Na 4 P 2 O 7 , K 3 PO 4 、Na 3 PO 4 , K 2 HPO 4 and Na 2 HPO 4 One or more of .

[0145] For example, the initiator used in preparing the graft copolymer latex and / or the conjugated diene rubber latex may be a water-soluble persulfate polymerization initiator, a fat-soluble polymerization initiator or a redox catalyst system. For example, the water-soluble persulfate polymerization initiator may include one or more selected from potassium persulfate, sodium persulfate and ammonium persulfate; the fat-soluble polymerization initiator may include one or more selected from cumene hydroperoxide, dicumyl hydroperoxide, azobisisobutyronitrile, tert-butyl hydroperoxide, p-menthane hydroperoxide and benzoyl peroxide; the redox catalyst system may include one or more selected from sodium formaldehyde sulfoxylate, sodium ethylenediaminetetraacetate, ferrous sulfate, glucose, sodium pyrrolidone and sodium sulfite.

[0146] In the method for preparing the graft copolymer and rubber latex, in addition to the above conditions, other reaction conditions, such as reaction time, reaction temperature, pressure and reactant addition time can be appropriately selected and used without particular limitation, as long as the other reaction conditions are commonly used in the field to which the present invention belongs.

[0147] For example, kneading and extrusion may be performed using a single screw extruder, a twin screw extruder, or a Banbury mixer. In this case, compatibility may be excellent due to uniform distribution of the composition.

[0148] For example, kneading and extrusion may be performed at a cylinder temperature of 200° C. to 250° C., preferably 210° C. to 240° C. In this case, the production amount per unit time may be appropriate, and melt kneading may be sufficiently performed. In addition, thermal decomposition of the resin component may be prevented.

[0149] For example, kneading and extrusion can be performed at a screw speed of 200 rpm to 300 rpm, preferably 230 rpm to 270 rpm. In this case, the production volume per unit time can be appropriate, and therefore, the process efficiency can be excellent. In addition, excessive cutting can be suppressed.

[0150] Molding

[0151] For example, the thermoplastic resin composition of the present invention can be used to produce the molded article of the present invention. In this case, mechanical properties, thermal stability and noise resistance can be maintained at a certain level, and chemical resistance, processability and injection moldability can be improved.

[0152] The molded article is preferably an automobile interior material, as a specific example, a center console or a door interior.

[0153] The method for producing the molded article preferably includes the steps of melt-kneading and extruding 20 to 40 wt % of a polyester resin (A); 15 to 30 wt % of a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); 20 to 35 wt % of an α-methylstyrene-vinyl cyanide compound copolymer (C); 10 to 20 wt % of a maleimide polymer (D); and 0.1 to 5 wt % of an amide lubricant (E) at 200 to 300° C. to prepare pellets and injecting the prepared pellets using an injection molding machine, wherein the molded article has a standard deviation of injection metering deviation of 2.4 or less or an average value of injection metering deviation of 18.3 or less when injection metering deviation of 30 shots is measured using a 600 MT injection molding machine at an injection temperature of 230° C. and a mold temperature of 50° C. In this case, physical property balance and injection molding processability can be excellent.

[0154] In describing the thermoplastic resin composition of the present invention, the method for preparing the same, and the molded article comprising the same, it should be noted that other conditions or equipment not explicitly described herein may be appropriately selected within the range generally practiced in the art without particular limitation.

[0155] Hereinafter, the present invention will be described in more detail with reference to the following preferred embodiments. However, these embodiments are provided for illustrative purposes only and should not be construed as limiting the scope and spirit of the present invention. In addition, it will be apparent to those skilled in the art that various changes and modifications may be made without departing from the spirit and scope of the present invention, and these changes and modifications are also within the scope of the appended claims.

[0156] [Example]

[0157] Materials used in the following Examples and Comparative Examples are as follows.

[0158] *A1: Polybutylene terephthalate (intrinsic viscosity: 1.0 dl / g)

[0159] *A2: Polybutylene terephthalate (intrinsic viscosity: 1.2 dl / g)

[0160] *B1: Acrylonitrile-butadiene-styrene graft copolymer (graft copolymer obtained by graft polymerization of 50 wt% of butadiene rubber, 30 wt% of styrene and 10 wt% of acrylonitrile, grafting degree: 39 wt%, weight average molecular weight: 78,000 g / mol)

[0161] *C1: styrene-acrylonitrile copolymer (acrylonitrile: 28 wt%)

[0162] *C2: α-methylstyrene-acrylonitrile-styrene copolymer (α-methylstyrene: 65 wt%, acrylonitrile: 28 wt%)

[0163] *D1: styrene-N-phenylmaleimide-maleic anhydride copolymer (styrene: 46 wt%, N-phenylmaleimide: 52 wt%, maleic anhydride: 2 wt%)

[0164] *E1: Polyethylene wax lubricant

[0165] *E2: Ethylene bis-stearamide lubricant

[0166] *Antioxidants: Phenolic antioxidants

[0167] *UV absorber: Hydroxyphenylbenzotriazole UV absorber

[0168] Examples 1 to 10 and Comparative Examples 1 to 7

[0169] According to the contents shown in Tables 1 and 2 below, the components shown in Tables 1 and 2 were fed into an extruder (42Ψ, barrel temperature: 230° C.) to obtain pellets, and the pellets were injected to obtain specimens for measuring physical properties.

[0170] [Test Example]

[0171] The physical properties of the samples prepared in Examples 1 to 10 and Comparative Examples 1 to 7 were measured according to the following methods, and the results are shown in Tables 1 and 2 below.

[0172] * Flowability (melt flow rate): The melt flow rate was measured under the conditions of 260° C. and 5 kg according to ISO 1133. Here, the unit of the melt flow rate is g / 10 min.

[0173] *Izod impact strength (KJ / m 2 ): Izod impact strength was measured at 23°C using notched test specimens according to ISO 180 / 1A.

[0174] *Tensile strength (MPa): The tensile strength was measured according to ISO 527 at 50 mm / min.

[0175] * Elongation (%): Elongation was measured at 50 mm / min according to ISO 527.

[0176] *Flexural Strength and Flexural Modulus (MPa): Flexural strength and flexural modulus were measured according to ISO 178 using 1 / 8″ thick specimens at a span of 64 mm and a test speed of 2 mm / min.

[0177] *Heat Deflection Temperature (°C): Heat deformation temperature was measured at 0.45 MPa according to ISO 75.

[0178] * Density (g / cm 3 ): Density is measured according to ISO 1183.

[0179] *ESC test (chemical resistance): A specimen having a size (length: 165 mm, width: 19 mm, thickness: 3.2 mm) equal to that of the tensile strength test specimen according to ASTM D638 was fixed to a fixture having a stress of 2.0%, 25 μl of an air freshener (containing a mixed solution of isoamyl acetate, limonene, and linalool in a volume ratio of 4:1:1) was applied to the specimen using a micropipette, and then, after 2 hours, the occurrence of cracks or cracks was observed with the naked eye. When no cracks or cracks occurred, it was marked as "○". When cracks or cracks occurred, it was marked as "X".

[0180] * Friction noise performance (stick-slip noise): Acceleration, pulse, frequency, friction, and fluctuation were measured using a Ziegler SSP-04 at a temperature of 23°C and a relative humidity of 50% using a flat specimen of 70 mm×60 mm and a flat specimen of 25 mm×50 mm, respectively, and the risk factor (RPN) value was calculated by the following equation 2, and then the friction noise performance was evaluated according to the following standard. At this time, the following four conditions were performed: the specimen load was 10 N and the moving condition was 1 mm / s; the specimen load was 10 N and the moving condition was 4 mm / s; the specimen load was 40 N and the moving condition was 1 mm / s; and the specimen load was 40 N and the moving condition was 4 mm / s.

[0181] [Equation 2]

[0182]

[0183] <Evaluation of friction noise performance>

[0184] RPN is 1 or more and 3 or less: Good (the probability of friction noise generation is very low)

[0185] RPN is 4 or more and 5 or less: Partially good

[0186] RPN is 6 or more and 10 or less: Not good

[0187] *Light fastness: According to MS210-05 or ISO 105, at a temperature of 89±3℃, a relative humidity of 50±5%, 84MJ / m 2 The radiation dose and 0.55±0.02W / m 2 The color difference change (ΔE) of each of the smooth sample and the embossed sample was measured under the condition of an irradiance of 1,000 grit to 40,000 grit. The smooth sample was prepared using a mold mirror-finished at 2,000 grit to 40,000 grit at an injection temperature of 230°C to 250°C and a mold temperature of 50°C. The embossed sample was prepared in the same manner as the above sample, except that a mold having an embossed pattern with a size of 15 μm to 21 μm formed on its surface was used.

[0188] When the color difference (ΔE) was measured, the color of the sample was determined using a Hunter Lab colorimeter, and ΔE was calculated by the following Equation 3.

[0189] [Equation 3]

[0190]

[0191] * Injection metering deviation: Injection metering deviation of 30 shots was measured using a 600MT injection molding machine at an injection temperature of 230°C and a mold temperature of 50°C, and its average and standard deviation were calculated.

[0192] [Table 1]

[0193]

[0194]

[0195] [Table 2]

[0196]

[0197]

[0198] [Table 3]

[0199]

[0200]

[0201] *During the injection process, the mold release of the injection molded product is poor.

[0202] As shown in Tables 1 to 3, the thermoplastic resin compositions according to the present invention (Examples 1 to 10) have excellent flexural strength, flexural modulus, heat deformation temperature, noise resistance, and injection moldability, compared with Comparative Examples 1 to 7 which are outside the scope of the present invention, while maintaining fluidity, impact strength, tensile strength, and elongation similar to those of the thermoplastic resin compositions of Comparative Examples 1 to 7.

[0203] As a remarkable result, in the cases of Examples 1 to 3 and 8 to 10 in which amide lubricants were used in the range of 0.5 to 2.0, the average value of the injection metering deviation (which is an indicator of the injection molding processability) was 16 or less, and the standard deviation thereof was 1.3 or less, showing excellent injection molding processability.

[0204] In contrast, in the case of Comparative Example 6 containing less than 0.1 wt% of the amide lubricant according to the present invention, the demolding property of the injection molded article was poor during the injection process. In the case of Comparative Example 7 containing more than 5 wt% of the amide lubricant according to the present invention, the chemical resistance was poor.

[0205] Furthermore, in the case of Comparative Examples 4 and 5 in which the polyester resin having an intrinsic viscosity of 1.0 dl / g was used, the impact strength was very poor.

Claims

1. A thermoplastic resin composition comprising a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D) and an amide lubricant (E), in, The thermoplastic resin composition comprises 20 to 40 wt % of the polyester resin (A), 15 to 30 wt % of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), 20 to 35 wt % of the α-methylstyrene-vinyl cyanide compound copolymer (C), 10 to 20 wt % of the maleimide polymer (D), and / or 0.1 to 5 wt % of the amide lubricant (E), wherein the polyester resin (A) has an intrinsic viscosity of 1.1 dl / g or more, and The weight of the polyester resin (A) is not less than the weight of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B).

2. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has an average value of injection metering deviation of 18.3 or less when injection metering deviation of 30 shots is measured at an injection temperature of 230° C. and a mold temperature of 50° C. using a 600 MT injection molding machine.

3. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has a heat distortion temperature of 108° C. or higher, measured at 0.45 MPa according to ISO 75.

4. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has a flexural strength of 66 MPa or more and a flexural modulus of 1,950 MPa or more when the flexural strength and flexural modulus are measured according to ISO 178 using a 1 / 8" thick test specimen under the conditions of a 64 mm span and a test speed of 2 mm / min.

5. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has a light resistance of 0.9 or less as measured according to MS210-05 (84 MJ, embossed specimen).

6. The thermoplastic resin composition according to claim 1, wherein The polyester resin (A) comprises one or more selected from polyethylene adipate (PEA), polybutylene succinate (PBS), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT) and polyethylene naphthalate (PEN).

7. The thermoplastic resin composition according to claim 1, wherein The vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound copolymer (B) is a graft copolymer obtained by graft-polymerizing 10 to 40 wt % of an aromatic vinyl compound and 1 to 20 wt % of a vinyl cyanide compound onto 40 to 80 wt % of a conjugated diene rubber.

8. The thermoplastic resin composition according to claim 1, wherein The α-methylstyrene-vinyl cyanide compound copolymer (C) contains 65 to 85 wt % of α-methylstyrene and 15 to 35 wt % of a vinyl cyanide compound.

9. The thermoplastic resin composition according to claim 1, wherein The maleimide-based polymer (D) comprises N-(substituted) maleimide and an aromatic vinyl compound.

10. The thermoplastic resin composition according to claim 1, wherein The amide lubricant (E) is a fatty acid amide lubricant.

11. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition includes 0.1 wt % to 5 wt % of one or more selected from an antioxidant and a UV absorber.

12. A method for preparing a thermoplastic resin composition, comprising melt-kneading and extruding a polyester resin (A), a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), an α-methylstyrene-vinyl cyanide compound copolymer (C), a maleimide polymer (D) and an amide lubricant (E) at 200° C. to 300° C., in, The thermoplastic resin composition comprises 20 to 40 wt % of the polyester resin (A), 15 to 30 wt % of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B), 20 to 35 wt % of the α-methylstyrene-vinyl cyanide compound copolymer (C), 10 to 20 wt % of the maleimide polymer (D), and / or 0.1 to 5 wt % of the amide lubricant (E), wherein the polyester resin (A) has an intrinsic viscosity of 1.1 dl / g or more, and The weight of the polyester resin (A) is not less than the weight of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B).

13. The method according to claim 12, wherein: The thermoplastic resin composition comprises 20 wt % to 40 wt % of the polyester resin (A); 15 wt % to 30 wt % of the vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (B); 20 wt % to 35 wt % of the α-methylstyrene-vinyl cyanide compound copolymer (C); 10 wt % to 20 wt % of the maleimide polymer (D); and / or 0.1 wt % to 5 wt % of the amide lubricant (E).

14. A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Heat resisting resin composition with improved glossiness and preparation thereof

    CN101503548A

  • Maleimide heat resisting resin composition with improved glossiness and preparation thereof

    CN101503551A